Synthesis of dominant plastic microfibre prevalence and pollution control feasibility in Chinese freshwater environments - Xu, Yuyao; Chan, Faith Ka Shun; Stanton, Thomas; Johnson, Matthew F.; Kay, Paul; He, Jun; Wang, Jue; Kong, Chuilan; Wang, Zilin; Liu, Dong; Xu, Yaoyang (Elsevier, 2021)
Microplastic pollution of freshwaters is known to be a great concern in China and these pollutants can be discharged into the coastal environment through fluvial processes, posing threats to the global marine ecosystem. This paper reviewed the literature measuring microplastic pollution in the Chinese freshwater environment and found that microfibres dominate other plastic morphologies in more than 65% of samples collected in surface water, sediments and effluents of wastewater treatment plants and domestic sewers. Current potential sources of microfibre pollution are identified including fishery activities, laundry sewage, and waste textiles according to previous research. Recommendations are offered using the circular economy management framework, such as textile waste reuse and recycling systems in China, for improving current control measures for microplastics in freshwaters.